Normative echocardiography data of myocardial adaptation to extrauterine life: a review of prospective studies - Suciu, Laura Mihaela; Prelipcean, Irina; Făgărășan, Amalia; Giesinger, Regan E.; McNamara, Patrick J. (Frontiers in Pediatrics, 2023)
Recent research has increased focus and interest in characterizing the physiology of the transition circulation using echocardiography. Critique of published normative neonatal echocardiography data among healthy term neonates has not been performed. We have performed a comprehensive literature review using the key terms: cardiac adaptation, hemodynamics, neonatal transition, term newborns. Studies were included if they had reported echocardiography indices of cardiovascular function in the presence of maternal diabetes, intrauterine growth restricted newborns and prematurity and had a comparison group of healthy term newborns within first seven postnatal days. Sixteen published studies evaluating transitional circulation in healthy newborns were included. There was marked heterogeneity in the methodologies used; specifically, inconsistency in time of evaluation and imaging techniques used makes it challenging to determine specific trends of expected physiologic changes. Some studies revealed nomograms for echocardiography indices, though limitations persist in terms of sample size, number of reported parameters and consistency of measurement technique. A comprehensive standardized echocardiography framework which includes consistent techniques for assessment dimensions, function, blood flow, pulmonary/systemic vascular resistance, and shunts pattern is warranted to ensure consistency in the use of echocardiography to guide care of healthy and sick newborns.